Annual proceedings of the Phytochemical Society of Europe (London, 1983)
The contributions of book concerne the structure of seed proteins, their localization, ontogenical evolution, molecular biosynthesis and degradation, improvement by breeding techniques and their technological properties. The book will be of interest to plant biochemists working with plant proteins in the human or animal nutrition field, food science and agriculture
Keywords: seeds - congresses